THE ART OF INVESTIGATION TECHNIQUE TO ENHANCE STUDENTS’ ACHIEVEMENT IN WRITING - KATEMBA, CAROLINE V. (LPPM Institut Seni Indonesia Padangpanjang, 2021)
ABSTRACTThis study entitled “The Art of Investigation Technique to Enhance Students’ Achievement in Writing”. This study intend to seek an answer to the questions “ Is there a significant difference in the enhancement of writing skills between the students who are taught using the Group Investigation technique and those who are taught through the conventional method?” This is an experimental study using classroom action research. The subject of this research were Grade VIII Students of SMP Negeri 1 Parongpong, Bandung. There were 75 students. To collect the data the pre-test was administered at the start of the program and the post-test at the end of the three months program. Based on the data analysis it was found that there was a significance difference among the experimental and the control groups. Another finding the students were interested in writing through Group Investigation Technique. Therefore it is concluded that teaching writing through Group Investigation Technique could improve students' writing skills. This study suggest that teachers of English should be trained to use this technique